Prognostic Impact and Prevalence of Cachexia in Patients With Heart Failure: A Systematic Review and Meta‐Analysis - Konstantinos Prokopidis; Krzysztof Irlik; Mirela Hendel; Julia Piaśnik; Gregory Y. H. Lip; Katarzyna Nabrdalik (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Cachexia, defined as the combination of weight loss, weakness, fatigue, anorexia and abnormal biochemical markers based on Evans' criteria, is known to exacerbate the prognosis of heart failure (HF) patients. This systematic review and meta‐analysis investigates the prognostic impact and prevalence of cachexia, as defined by Evans' criteria, in patients with HF. Methods PubMed, Cochrane Library, Scopus and Web of Science were searched from inception until December 2023, including HF patients for whom the Evans' criteria were applied to explore the prevalence and prognostic impact of cachexia. This study employed a meta‐analyses using the random‐effects model and inverse‐variance method that was adhered to the revised 2020 PRISMA guidelines for systematic reviews and meta‐analyses (CRD42023446443). Results Six prospective or retrospective studies of 2252 patients with HF were included, whereby all‐cause mortality was significantly greater in patients with cachexia with low heterogeneity among studies (HR: 1.60, 95% CI 1.31–1.95, p < 0.001; I2 = 0%). For the studies that used full, uniformly defined Evans' criteria, among 1844 patients, mortality remained greater in patients with cachexia (HR: 1.58, 95% CI 1.27–1.97, p < 0.001; I2 = 0%). In a subgroup analysis among 1714 of HF with reduced ejection fraction, the results were consistent (HR: 1.57, 95% CI 1.28–1.92, p < 0.001; I2 = 0%). Additionally, 10 studies comprising 2862 patients indicated a 31% risk of cachexia in HF (95% CI 21–43%, I2 = 94%). Conclusions Cachexia is an independent predictor for increased all‐cause mortality among patients with HF with a notable prevalence of 31%. Interventions aiding in improving fatigue, anorexia and exercise capacity could help improve the quality of life of this clinical population.